PENGARUH DISIPLIN DAN KOMPETENSI TERHADAP KINERJA GURU DI MADRASAH TSANAWIYAH ITTIHAADUL ULUM KOTA LUBUKLINGGAU - Aminatuzzuhro Aminatuzzuhro; Gunadi Gunadi (Jurnal Interprof, 2017)
The research objective to be achieved are as follows: the objectives of this research are: 1) To determine the effect of discipline and competence of the performance of teachers at MTs Ittihaadul Ulum Lubuklinggau. 2) To determine the effect of discipline on the performance of teachers at MTs Ittihaadul Ulum Lubuklinggau. 3) To determine the effect of competence on the performance of teachers at MTs Ittihaadul Ulum Lubuklinggau. T test results can be explained that the discipline variables (X1) on teacher performance showed the value t = 10.414 is greater than the value ttable 2,042 with a significant level = 0.000 <(α) 12:05, df (n-2) 35-2 = 33 amounted to 2,042 , suggesting that Ho is rejected and Ha accepted and partially discipline variables have a significant effect on the performance of teachers at MTs Ittihaadul Ulum Lubuklinggau.Kemudian City t test results above can be explained that the competence variable (X2) on teacher performance showed the value t = 5,575 greater than the value ttable 5,575 with a significant level = 0.000 <(α) 12:05, df (n-2) 35-2 = 33 is equal to 2.042, suggesting that Ho is rejected and Ha accepted and in partial competency has significant influence the performance of teachers at MTs Ittihaadul Ulum Lubuklinggau. Further testing of the hypothesis that Fhitung obtained is 87.116> F table = 3.30 significance level simultaneously and significance is 0.000 <(α) = 0.05 df = n - k = 35 - 2-1 = 32 amounted to 3.30 so Ho rejected and Ha accepted. means shows that together (simultaneously) the independent variable X1 (discipline) and X2 (competence) have a significant effect on the dependent variable Y (the teacher's performance) so the hypothesis proved to be true and acceptable.